Pengaruh Kompetensi Pegawai dan Disiplin Kerja terhadap Efektivitas Kerja Pegawai pada Kantor Imigrasi Kelas I Jakarta Utara - Zaman Zaini; Rida Agustian (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
The purpose of this study to determine the meaning of Employee Competency And Discipline Work Against Employee Effectiveness. The theory used in this research is to describe Mc Ashan in Mulyasa on Employee Competence, Soegeng on Work Discipline and McGregor on the effectiveness of employee's work.           The method used in this research is quantitative method through survey, with population of 70 sample with saturated sample or whole population used as sample and research instrument using Likert Scale.           With the help of SPSS application version 2.3 for windows shows that: partially t test result show that employee competence have influence and signifikan to work effectiveness of employees equal to 61,8%, because bigger than t table. Partially, the two t test results show that work discipline has a positive and significant effect on the effectiveness of employee work is 69.0% because it is bigger than t table. Competence free variable and Discipline work together Fisting effect on the effectiveness of employee work equal to 70,4%, because Fhitung bigger than F table.